2016
DOI: 10.1021/acs.est.5b04969
|View full text |Cite
|
Sign up to set email alerts
|

A Methodology for Robust Comparative Life Cycle Assessments Incorporating Uncertainty

Abstract: We propose a methodology for conducting robust comparative life cycle assessments (LCA) by leveraging uncertainty. The method evaluates a broad range of the possible scenario space in a probabilistic fashion while simultaneously considering uncertainty in input data. The method is intended to ascertain which scenarios have a definitive environmentally preferable choice among the alternatives being compared and the significance of the differences given uncertainty in the parameters, which parameters have the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 24 publications
0
50
0
Order By: Relevance
“…As shown here, the overlap area uses quantitative uncertainty information, which can derive from inventory, characterization, and/or methodological choices (Mendoza Beltran et al 2016). We can identify relevant aspects of a comparison with the overlap area between probability distributions or other approaches that evaluate mutual differences (Heijungs and Kleijn 2001;Prado-Lopez et al 2014;Henriksson et al 2015;Gregory et al 2016;Wei et al 2016). These results do not suffer from the systematic biases of external normalization, as the outputs vary for each LCA application (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown here, the overlap area uses quantitative uncertainty information, which can derive from inventory, characterization, and/or methodological choices (Mendoza Beltran et al 2016). We can identify relevant aspects of a comparison with the overlap area between probability distributions or other approaches that evaluate mutual differences (Heijungs and Kleijn 2001;Prado-Lopez et al 2014;Henriksson et al 2015;Gregory et al 2016;Wei et al 2016). These results do not suffer from the systematic biases of external normalization, as the outputs vary for each LCA application (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, discernibility analysis (Heijungs and Kleijn 2001) counts the times in which one alternative is greater than another in each Monte Carlo run. Following the same basis, but illustrating a more extensive approach with sensitivity analysis is the approach shown in Gregory et al (2016). The relevance parameter as introduced in PradoLopez et al (2014) evaluates the ratio of the differences in means to the standard deviations.…”
Section: Overlap Area Approachmentioning
confidence: 99%
“…There concluded that there is a need both for more accurate simulation models and for procedural methods that integrate the energy results with other decisions. Gregory et al [45] used a decision-tree algorithm to compare alternative solutions in a life cycle perspective. This approach identified the most influential parameters in the scenarios, including parameters related to system boundaries.…”
Section: Methodsmentioning
confidence: 99%
“…The approach allows a simplification of multicriteria problems, reducing the computational time to identify the best options. As mentioned above, Gregory et al [45] proposed a methodology for making robust decisions under uncertainty, based on decision-tree algorithms and probability distributions. This method can also be used to address multicriteria decision problems.…”
Section: Methodsmentioning
confidence: 99%
“…This is particularly important as many economies strive towards circularity, where LCA systems will encounter more often multifunctional processes (Mendoza Beltran et al 2015). Despite some other studies treating uncertainty sources such as methodological choices, modeling assumptions, and inventory data u n c e r t a i n t y, b y m e a n s o f d i ff e r e n t a p p r o a c h e s (Andrianandraina et al 2015;Gregory et al 2016), we are not aware of any study so far treating uncertainty due to the choice of allocation method for all multi-functional background processes.…”
Section: Comparative Lcas With Uncertainty Analysismentioning
confidence: 99%